2017
DOI: 10.1038/s41467-017-01373-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimal coding and neuronal adaptation in economic decisions

Abstract: During economic decisions, offer value cells in orbitofrontal cortex (OFC) encode the values of offered goods. Furthermore, their tuning functions adapt to the range of values available in any given context. A fundamental and open question is whether range adaptation is behaviorally advantageous. Here we present a theory of optimal coding for economic decisions. We propose that the representation of offer values is optimal if it ensures maximal expected payoff. In this framework, we examine offer value cells i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 58 publications
(80 reference statements)
5
107
0
Order By: Relevance
“…In these conditions, two groups of cells in OFC encode the offer values of juices A and B (Padoa-Schioppa and Assad, 2006;Padoa-Schioppa, 2013). Importantly, their tuning curves are quasi-linear and the gain is inversely proportional to the value range (range adaptation) (Padoa-Schioppa, 2009;Rustichini et al, 2017). Moreover, cells in each group adapt to their own value range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these conditions, two groups of cells in OFC encode the offer values of juices A and B (Padoa-Schioppa and Assad, 2006;Padoa-Schioppa, 2013). Importantly, their tuning curves are quasi-linear and the gain is inversely proportional to the value range (range adaptation) (Padoa-Schioppa, 2009;Rustichini et al, 2017). Moreover, cells in each group adapt to their own value range.…”
Section: Resultsmentioning
confidence: 99%
“…Here we formalize the prediction illustrated in Fig.3. As a premise, previous work found that the tuning curves of offer value cells in OFC are quasi-linear (Rustichini et al, 2017) and the proportion of neurons presenting positive versus negative encoding is roughly 3:1 (Padoa-Schioppa, 2013;Ballesta and Padoa-Schioppa, 2019). Importantly, cells in each group adapt to their own range, not to the maximum range (Conen and Padoa-Schioppa, 2019).…”
Section: Supplementary Note: Range-dependent Effects Of Electrical Stmentioning
confidence: 91%
“…These context effects allow efficient coding of broad ranges of sensory input and are well documented in perception (see, e.g., Carandini and Heeger, 2012;Louie and Glimcher, 2012). Recently, context--dependence and normalization were reported also in value--based decision, in both monkeys (Padoa--Schioppa, 2009;Bermudez and Schultz, 2010;Kobayashi et al, 2010;Rustichini et al, 2017;Conen and Padoa--Schioppa, 2019) and humans (Nieuwenhuis et al, 2005;Elliott et al, 2008;Cox and Kable, 2014;Burke et al, 2016; see Louie and De Martino, 2014 for a review), allowing optimal responses to vast ranges of values in PFC. Specifically, neurons seem to rescale their firing to adapt to the decision context (relative coding) so that their response to a specific value depends on the choice context (e.g., reward vs. punishment), rather than being invariant (absolute coding).…”
Section: Introductionmentioning
confidence: 90%
“…There is increasing evidence that dynamic remapping of representational range occurs along more abstract dimensions, such as value 25,26,27,28,29 , numerosity 30,31 , relative frequency 32 , and variance 33 .…”
mentioning
confidence: 99%